Hematology and blood chemistry of Japanese quail (Coturnix coturnix japonica) (Revista Sistemas de Producción Agroecológicos, 2016)
This work was performed in order to determine the values of hematology and blood chemistry of Japanese quail in the Villavicencio city, because at present no are found results of studies on this issue conducted in the country and especially in the Orinoco´s region, at a time determines how metabolism can be affected, when essential components of the diet as are the amino acids L-lysine and DL-methionine are at different levels. 36 quail 45 days old were used, with an average weight of 155.5 g, in a completely randomized experimental design with three treatments, four replicates and three birds per experimental unit. The treatments were composed of basal diet 1.036% of lysine and 0.393% of methionine. Analysis of variance was performed using statistical analysis software Statisitical Sistem Analysis, SAS®. The variables evaluated were total count of erythrocytes, hemoglobin, hematocrit, mean corpuscular volume, thrombocytes, differential leukocyte count, glucose, lactose, calcium, potassium, sodium, total carbon dioxide, bicarbonate, oxygen saturation, partial pressure dioxide carbon and blood pH. In conclusion supplementation of synthetic amino acids L-lysine and DL-methionine increases the percentage of blood oxygen saturation, and levels of 0.153% lysine in the diet may favor the immune system of Japanese quail in stance phase, preventing the appearance of pathologies that affect production systems.
Keywords: metabolic profiles; amino acid; methionine; lysine; egg